2014
DOI: 10.9734/bjmmr/2014/7035
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functions, Sexual Organs and Sex Hormone Level in Chronic Alcohol Intake

Abstract: A general knowledge among youths is that alcohol enhances sexual desire and sexual performance. In contrast to this, studies have reported various adverse effects of alcohol on reproductive and sexual functions in both male and female. Male alcoholics frequently suffer from erectile dysfunction, intermittent delay in or absence of orgasm, and premature or delayed ejaculation. Alcohol is a toxin that can damage sperm-producing cells in the testicles, decrease testicular size, increase number of abnormally-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Ethanol intoxication affects the hormonal levels of estrogen and progesterone, which leads to hyperprolactinemia (Olusola et al 2014). Previously, it has been suggested that the optimal blood level of FSH is known to be a prerequisite for initiation and maintenance of normal ovarian folliculogenesis (Monfared and Salati 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol intoxication affects the hormonal levels of estrogen and progesterone, which leads to hyperprolactinemia (Olusola et al 2014). Previously, it has been suggested that the optimal blood level of FSH is known to be a prerequisite for initiation and maintenance of normal ovarian folliculogenesis (Monfared and Salati 2013).…”
Section: Discussionmentioning
confidence: 99%